Reduce Anxiety about Public Speaking through Group Guidance Using Symbolic Modeling Techniques - Muhamad Ihsan; Raudah Zaimah Dalimunte; Meilla Dwi Nurmala (Ma'soem University, 2022)
The research was based on the results of interviews in the pre-study. It was found that there were still students who had anxiety in public speaking in class VI SD Negeri 1 Sajira, Lebak Regency, in the 2021/2022 academic year. This study aimed to determine the effectiveness of group guidance with symbolic modeling techniques to reduce public speaking anxiety. This study uses a pre-experimental research design with One Group Pre-test-Post-test Design. Determination of the sample using the purposive sampling method. The research subjects comprised six students with a high public speaking anxiety category and two students with low public speaking anxiety. The method of data collection in the study was obtained through a questionnaire. Research results showed an average of 115. On the pre-test, with a percentage of 93%, while 51 with a percentage of 73% in the post-test. Grade VI students of SD Negeri 1 Sajira, Lebak Regency, for the 2021/2022 academic year. For future researchers, this research can be developed using different techniques to obtain better results. Furthermore, future researchers are expected to be able to enrich the literature review on public speaking anxiety by developing the approach applied.